Pengaruh Beban Kerja Dan Organizational Citizenship Behaviour (Ocb) Terhadap Kepuasan Kerja Pegawai Rsud Serpong Utara - Fajar Julianto; Styo Budi Utomo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to determine the effect of organizational citizenship behavior (OCB) and workload on job satisfaction of North Serpong Regional Hospital employees, both partially and simultaneously. This research method uses a quantitative method with a sample of 100 respondents, data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, simple correlation coefficient test, multiple correlation coefficient test, determination coefficient analysis test, t test and f test. Based on the results of the t test, the calculated t is 11.150>1.984 and the significance value for the workload variable (X1) is 0.000, a significant value smaller than the probability value of 0.05 or 0.000<0.05, thus Ho is rejected and H1 is accepted, meaning that the organizational citizenship behavior (OCB) variable (X1) has a positive and significant effect on the job satisfaction variable (Y) at North Serpong Regional Hospital. Based on the results of the t test, the calculated t value was 11.490>1.984 and the significance value for the organizational citizenship behavior (OCB) variable (X2) was 0.000, the significance value was smaller than the probability value of 0.05 or 0.000<0.05, meaning that the organizational citizenship behavior (OCB) variable (X2) had a positive and significant effect on the job satisfaction variable (Y) at North Serpong Regional Hospital. Based on the results of the f test, the calculated f value was 78.889>3.09 and the significance value was 0.000<0.05. So it can be concluded that the workload variable (X1) and organizational citizenship behavior (OCB) (X2) simultaneously have a positive and significant effect on job satisfaction (Y) at North Serpong Regional Hospital.